2013
DOI: 10.1097/tp.0b013e318291a2da
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Knee Osteoarthritis With Autologous Mesenchymal Stem Cells

Abstract: MSC therapy may be a valid alternative treatment for chronic knee osteoarthritis. The intervention is simple, does not require hospitalization or surgery, provides pain relief, and significantly improves cartilage quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
256
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(267 citation statements)
references
References 47 publications
8
256
0
3
Order By: Relevance
“…34,35 Some studies include case series and clinical trials with BM mesenchymal cells; some of them administered the cells by means of surgical intervention 13,[36][37][38] and others with intra-articular injection. 12,[39][40][41][42] We evaluated our results by means of VAS and WOMAC scales, since these have been used in many other knee OA studies, 40 in order to determine knee function and pain, and found that there was an improvement from the first week in the BM-SC group. In this setting it is possible that SCs have an antiinflammatory effect, which could explain the short-term clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Some studies include case series and clinical trials with BM mesenchymal cells; some of them administered the cells by means of surgical intervention 13,[36][37][38] and others with intra-articular injection. 12,[39][40][41][42] We evaluated our results by means of VAS and WOMAC scales, since these have been used in many other knee OA studies, 40 in order to determine knee function and pain, and found that there was an improvement from the first week in the BM-SC group. In this setting it is possible that SCs have an antiinflammatory effect, which could explain the short-term clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) scans performed one year after the surgical intervention showed significantly better Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) scores for the cell-recipient group than the microfracture alone group (28 patients) [76]. In a pilot study of 12 OA patients with intra-articular injection of 40 million autologous expanded BM-MSCs, the patients showed a large improvement in algofunctional indices by one year, and MRI scanning exhibited a 27% decrease in poor cartilage areas with improvement of cartilage quality in 11 of the 12 patients [77]. Most recently, two clinical trials have attracted a lot of interest.…”
Section: Msc Therapy For Oamentioning
confidence: 96%
“…26,27 Intra-articular injection of autologous MSCs in to the knee joints of patients with OA has been well tolerated and a significant reduction in pain has been observed, with paracrine anti-inflammatory activity of MSCs postulated to contribute to this outcome. [28][29][30] Furthermore, treatment of patients undergoing partial meniscectomy surgery with an intra-articular injection of allogeneic MSCs has resulted in meniscal regeneration as well as a significant reduction in pain. 31 To achieve successful regeneration with tissue engineering approaches in an osteoarthritic joint, an in-depth understanding is required of how OA-associated inflammation impacts chondrocyte and progenitor cell behavior.…”
Section: -24mentioning
confidence: 99%